Part-time prospects : an international comparison of part-time work in Europe, North America and the Pacific Rim - O'Reilly, Jacqueline; Fagan, Colette (Routledge, 1998)
The growth in part-time employment has been one of the most striking features in industrialized economies over the past forty years. Part-Time Prospectspresents for the first time a systematically comparative analysis of the common and divergent patterns in the use of part-time work in Europe, America and the Pacific Rim. It brings together sociologists and economists in this wide-ranging and comprehensive survey. It tackles such areas as gender issues, ethnic questions and the differences between certain national economies including low pay, pensions and labour standards.